Evaluation of sampling and analysis techniques for early detection of Limnoperna fortunei (Mytilidae) in limit areas of its distribution - Darrigran, Gustavo (2009)
The golden mussel Limnoperna fortunei (Dunker, 1857) (Mytilidae) is an invading species in continental waters in the Neotropical Region. L. fortunei is transported by human activities. Differing from fresh water bivalves native to the region, this mytilid has external fertility and a planktonic larval development similar to marine mytilids (Monteiros-Ribas et al.. 2006). The impact produced by L. fortunei on numerous South American rivers includes, among others, alteration of benthonic communities, alteration of fish diet, as well as severe macrofouling problems at industrial water intakes (Darrigran. 2002). Thus, it is fundamental to know the dynamic distribution of this invading species to explain its invading process and to have access to basic information to predict its distribution/ dispersion pattern.